SOCIAL DISCRIMINATION IN MARGOT LEE SHETTERLY’S HIDDEN FIGURES - Citra Seliyana Sofia Suhadi; Ceisy Wuntu; Agustine C. Mamentu (Program Studi Pendidikan Bahasa Inggris, 2022)
The aim of the research is to uncover the social discrimination in Margot Lee Shetterly's Hidden Figures. The writer used qualitative research in this study because the data was collected in the form of words. This means that, unlike quantitative research, this study does not use numbers or diagrams. The writer used two types of sources to gather the information. The novel Hidden Figures is the first source, and relevant books that support the writer's research are the second. The skripsi revealed the social discrimination faced by African American women in the novel. Inequality in educational facilities, inequity in welfare benefits, gender discrimination in the workplace and Responding problem with big resilient. In the 1940s, African American women were subjected to racial discrimination as a result of unfair treatment, unjust policies, and segregation in public facilities. Because they are in segregated educational settings, Dorothy Vaughan, Katherine Goble, and Mary Jackson have restricted opportunities to improve their capabilities. Women are also relegated to the second class in the workplace, where they endure discrimination in the form of divided cafeterias, segregated restrooms, and a lack of recognition or credit for their efforts. Dorothy Vaughan and her family member, Matilda West, are blamed as socialists in the study since she overcomes the gloomy strengthening. This type of dishonest indictment might be seen as a form of racial segregation, because black people are disproportionately affected.